Developing Long Term Low Emissions and Climate Resilient Agricultural Development Pathways for Ghana: The right data at the right time - African Group of Negotiators Expert Support; Food and Agriculture Organization of the United Nations; Accelerating Impacts of CGIAR Climate Research for Africa (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Ghana embarked on a journey of developing its Agriculture Sector Low Term Low Emissions and Climate Resilient Development Pathways (Agriculture LTS) aimed at facilitating the country’s transformation to a green economy by prioritising adaptation and mitigation actions that increase agricultural productivity and build climate resilience of the agricultural and food systems while reducing greenhouse gas (GHG) emissions intensity in the agriculture sector. The development of the Agriculture LTS that shows when emissions will be peaking is a proactive step in setting the country on a trajectory that transform her agriculture sector in a way that increases agricultural productivity and builds climate resilience while reducing emissions intensity in the sector. The Agriculture LTS provides the enabling framework for local and national stakeholders to identify development strategies and actions suitable for growth in a changing climate.